2023
DOI: 10.1038/s41598-023-42833-4
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of CviR-mediated quorum sensing inhibitors from Cladosporium spp. against Chromobacterium violaceum through computational studies

Mahadevamurthy Murali,
Faiyaz Ahmed,
Hittanahallikoppal Gajendramurthy Gowtham
et al.

Abstract: An opportunistic human pathogenic bacterium, Chromobacterium violaceum resists the potency of most antibiotics by exploiting the quorum sensing system within their community to control virulence factor expression. Therefore, blocking the quorum sensing mechanism could help to treat several infectious caused by this organism. The quorum sensing receptor (CviR) of C. violaceum was used as a model target in the current investigation to identify potentially novel quorum sensing inhibitors from Cladosporium spp. th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Further, the MM-PBSA analysis of the lead metabolite (Aspochalasin M)/ standard inhibitor (Erlotinib)–bound EGFR tyrosine kinase domain complex trajectories of the last 20 ns (80–100 ns) MD simulations were performed to determine the complex’s thermodynamics parameters such as van der Waals energy (E vdw ), electrostatic energy (E Elec ), polar solvation energy (ΔE Polar ), SASA energy and binding free energy (ΔE Binding ), all of which are expressed as kcal/mol ( Table 3 ). Compared to other energies, van der Waals energy was the main driver of complex formation [ 47 , 48 ] and it can be inferred that the binding energy and van der Waals energy significantly influenced the complex formation. Based on energy calculation, the expected outcomes were largely beneficial from an energetic standpoint.…”
Section: Resultsmentioning
confidence: 99%
“…Further, the MM-PBSA analysis of the lead metabolite (Aspochalasin M)/ standard inhibitor (Erlotinib)–bound EGFR tyrosine kinase domain complex trajectories of the last 20 ns (80–100 ns) MD simulations were performed to determine the complex’s thermodynamics parameters such as van der Waals energy (E vdw ), electrostatic energy (E Elec ), polar solvation energy (ΔE Polar ), SASA energy and binding free energy (ΔE Binding ), all of which are expressed as kcal/mol ( Table 3 ). Compared to other energies, van der Waals energy was the main driver of complex formation [ 47 , 48 ] and it can be inferred that the binding energy and van der Waals energy significantly influenced the complex formation. Based on energy calculation, the expected outcomes were largely beneficial from an energetic standpoint.…”
Section: Resultsmentioning
confidence: 99%
“…The re-docking study confirmed that the potential compounds and positive control showed the same binding energy with RMSD values between ≤2.0 Å, which agrees with the findings of Ramírez and Caballero (2018) . Recently, Murali et al (2023) have intended to identify the effective inhibitors of quorum sensing from 123 bioactive compounds of Cladosporium spp. against C. violaceum through computational studies and noted that six compounds had higher docking score than Azithromycin, suggesting their strong affinity towards the CviR protein.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the predicted toxicity parameters of the drug were AMES toxicity, maximum human tolerated dose, human Ether-à-go-go Related Gene (hERG) I and II inhibitors, oral rat acute toxicity (LD 50 ) and chronic toxicity (LOAEL), hepatotoxicity, skin sensitization, Tetrahymena pyriformis toxicity and minnow toxicity. Ames test is a robust bacterial bioassay used to identify possible carcinogens by studying their mutagenic effect on bacteria [ 70 , 71 ]. The predicted results suggested that Kumudine B was expected to be AMES test negative; thus, it was non-mutagenic and may not act as a carcinogen compared to Streptomycin.…”
Section: Resultsmentioning
confidence: 99%